Short-term efficacy of right-to-left shunt closure in patients with vestibular migraine - Lang, Yilin; Zhang, Sai; Xie, Peifan; Wang, Yang; Wang, Chuangwei; Wang, Wenting; Zhu, Xien; Gu, Ping (Frontiers in Neurology, 2024)
ObjectiveThis study aims to evaluate the short-term efficacy of right-to-left shunt closure in vestibular migraine patients, and compare the efficacy between patent foramen ovale (PFO) closure and pulmonary arteriovenous malformation (PAVM) embolization. Additionally, the study identifies factors related to surgical outcomes.MethodsForty-one patients with vestibular migraine and medium to large right-to-left shunts underwent surgery: PFO closure, PAVM embolization, or both. Baseline data and postoperative outcomes at one month, including migraine and dizziness frequency, duration, VAS, HIT-6, migraine scores, and DHI scores, were analyzed. The correlation between efficacy and baseline data was analyzed.ResultsAt one month postoperatively, the frequency and duration of dizziness and migraine attacks significantly decreased, and the VAS, HIT-6, migraine scores, and DHI scores all significantly dropped (p < 0.001). There was no significant difference in the improvement rates of VAS, HIT-6, migraine scores, and DHI scores between the PFO group and the PAVM group (p > 0.05). Red blood cell parameters positively correlated with the improvement rates of VAS, HIT-6, migraine scores, and DHI. This approach was more effective in male patients than in female patients (p < 0.05).ConclusionRight-to-left shunt closure has a significant short-term effect on patients with vestibular migraine, regardless of the shunt location. Red blood cell parameters may serve as predictive indicators for the surgical efficacy in these patients.